Influence of structural parameters of electro-hydraulic diesel fuel injector on set of diagnostic parameters - B. V. Zhuravsky (Вестник СибАДИ, 2023)
Introduction. Malfunctions of the elements of the fuel injection system lead to a deterioration in the performance of diesel engines. The largest proportion of faults that occur during the operation of battery injection systems are electro-hydraulic injectors. For the timely detection of malfunctions, the injectors are diagnosed. The most accurate determination of the technical condition of the injectors can be made using specialized diagnostic stands with their removal from the engine. As a rule, the diagnosis is a conclusion about the general technical condition of the injector. To ensure high quality and reduce the complexity of repairs, it is necessary to use new methods and tools that allow for in-depth diagnostics of injectors with the identification of specific defects. The purpose of the presented work is to identify possible differences in the change in the set of diagnostic parameters when changing individual structural parameters in order to be able to determine specific defects in injectors during their diagnosis.Materials and methods. The hydrodynamic processes occurring in the electro-hydraulic injector during its operation were described by a system of differential equations of the first order. Numerical experiments were carried out to study the influence of changes in structural parameters on diagnostic parameters. The calculations using the software environment for mathematical calculations Mathcad were carried out. The calculations at different combinations of pressures in the fuel accumulator and the duration of the control pulse corresponding to certain engine operating modes were carried out.Results. The paper presents the graphs of the dependences of the cyclic supply, the average fuel consumption in the drain line, the delay in the start of the needle lift, the duration of the needle lift and landing, the duration of the injection and the sensitivity of these diagnostic parameters on the gaps in the interfaces ‘needle guide spray body’, ‘plunger multiplier – sleeve’, from the magnitude of the leakage of the control valve.Discussion and conclusion. As a result of numerical experiments, differences in the change in the set of diagnostic parameters with a change in individual structural parameters were found.